Platelets characteristics in patients with coronary artery disease and atrial fibrillation - I. O. Melnychuk (Сучасні медичні технології)
The aim. To estimate the connections between platelet morphological characteristics and amino acids (AA) profile in patients with coronary artery disease (CAD) and atrial fibrillation (AF).